Case Report: A New Tool for Anterior Chest Wall Reconstruction After Sternal Resection for Primary Or Secondary Tumors - Divisi, Duilio; Tosi, Davide; Zaccagna, Gino; De Vico, Andrea; Diotti, Cristina; Crisci, Roberto (Frontiers in Surgery, 2021)
Sternal resection and anterior chest cage reconstruction techniques for malignant processes are not always standardized. In this work we report an innovative method of sternal osteosynthesis in 65-year-old woman with Ewing's sarcoma and in 41-year-old woman with infiltrating thymoma. The first case manifested itself as a voluminous palpable mass while the second case was characterized for a paramediastinal mass widely extended to the anterior chest wall. Reconstruction with titanium mesh allowed the quick restoration of parietal stability, facilitating respiratory dynamic and recovery of patients.